2018
DOI: 10.1142/s012906571750054x
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Phrase Quadrature Perception in Harmonic Rhythm: An EEG Study Using a Brain–Computer Interface

Abstract: For the sake of establishing the neural correlates of phrase quadrature perception in harmonic rhythm, a musical experiment has been designed to induce music-evoked stimuli related to one important aspect of harmonic rhythm, namely the phrase quadrature. Brain activity is translated to action through electroencephalography (EEG) by using a brain-computer interface. The power spectral value of each EEG channel is estimated to obtain how power variance distributes as a function of frequency. The results of proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…EEG connectivity features were reported to play an essential role in the recognition tasks [37]. Another study, using the same device, observed a correlation of EEG with classical music rhythm [38], [39]. Music therapy is one of the applications emanating from music-elicited emotion [40].…”
Section: Consumer Grade Eeg For Emotion Recognitionmentioning
confidence: 99%
“…EEG connectivity features were reported to play an essential role in the recognition tasks [37]. Another study, using the same device, observed a correlation of EEG with classical music rhythm [38], [39]. Music therapy is one of the applications emanating from music-elicited emotion [40].…”
Section: Consumer Grade Eeg For Emotion Recognitionmentioning
confidence: 99%
“…Thus, we expect that parameters or measures with different origins are considered in a multivariate way [ 1 , 4 ]. Furthermore, recent developments in sensor technology enabling routine recordings of multi-channel signals have led to an increasing popularity of this kind of analysis on physiological data [ 1 , 2 , 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This paper introduces arousal detection from EDA signals using musical stimuli. Several studies have reported that using music to elicit emotions is one of the most effective methods of emotion induction [27][28][29][30]. Music plays a key role in most people's lives, frequently being used to explore and regulate emotions.…”
Section: Introductionmentioning
confidence: 99%